SHAPING THE NEW TREND OF DIGITAL MEDIA IN ENGLISH TEACHING - Venny Eka Meidasari (Universitas Negeri Padang, 2015)
This paper focuses on shaping of the new trend of digital media in English teaching and finding the best ways to take advantages from the technologies in pedagogical framework. The new trend of digital media technologies including social networks (e.g. Second Life, Facebook. Twitter) offer opportunities for teachers to challenge previous centralized models of learning by connecting. sharing and discussing ideas with their students outside of the classroom and at great distance from each other. New digital media have become an important part in the life of our young generation. lt is a natural for teachers to take a close look at the trend and take it into consideration when lessons are conceptualized. By using these media, teachers are offered a great possibility to increase motivation, oral participation and thus language competence in almost every field. Our failure to provide language learning material resources must partly be due to teachers and parents who either do not appreciate or do not understand the power of social media. In this paper, I try to explore the importance of shaping the new trend of digital media in teaching English not just simply because the students are confronted with new digital media in their daily life anyway, but because of the fact that the more channels for the reception of information are used, the better for the students' language acquisition or their learning process in general.